Food Stall Operations Practices in a Province-Based Food Park in the Philippines - Jesus P Briones; Fides C De Mesa; Mildred D Gamalando; Eric G Seco; Joanna Paula E Verano (Logistic and Operation Management Research (LOMR), 2025)
Food parks have been on the rise for several years, offering small business owners an opportunity to cater to consumers’ diverse food preferences. This study assessed food stall operations practices in a province-based food park in the Philippines. Using a quantitative-descriptive research design, the study examined the operational practices and challenges of 76 food stall businesses located in the subject food park. A self-structured questionnaire in Google Forms was distributed online to the respondents via a group chat set up by the food park operator. Data analysis included frequency distribution, percentage, weighted mean, and multiple regression. Findings revealed that food stall operators effectively practiced strategies in operation management and revenue generation, customer engagement and regulatory compliance, while financial planning and sustainability, and competitive market positioning were areas that needed improvement. Moreover, respondents experienced moderate operational challenges, highlighting the need for effective strategies to address such challenges. Additionally, a strong correlation between location and mobility and operational challenges in terms of regulatory compliance was revealed, underscoring the importance of strategic location in reducing operational barriers for the survival of food stall businesses. However, other food stall operations practices were not significantly related to operational challenges. In light of these findings, the study proposed strategies to boost profitability, operational efficiency, and resilience in food stall businesses, emphasizing the importance of strategic planning and best practices for the success and development of the food park industry.